Experimental Study on the Safety Assessment of Reinforced Concrete Shear Wall Structure with the Correspondence between Damage Image and Index - Suxia Kou; Jianmin Zhang; Jing Ren (Advances in Civil Engineering)
The post-disaster emergency rescue and loss evaluation hinges on the timeliness and accuracy of safety assessment of building structures in quake-hit regions. At present, the damage identification of quake-hit buildings in China is mainly conducted based on the experience of the experts. Such an assessment method will inevitably lead to the differences in identification results because each expert has his/her own subjective understanding of the degree of structural damage. In order to solve this problem, the low cyclic loading test of 7 specimens of shear wall is conducted and the hysteretic curves of seven shear walls are drawn. The failure modes and seismic performance of members under different design parameters (axial compression ratio of shear wall, shear span ratio, form of edge member, reinforcement ratio, stirrup ratio of coupling beam, and span height ratio) are compared. By recording the damage images taken at the controlled displacement under each level of load, the corresponding damage indexes are calculated, and the correspondence between the typical component damages and the damage indexes is discovered. After that, the images are compiled into an atlas. The authors calculate the damage index of the overall structure based on the damage indexes of the components and carries out damage identification of RC shear wall structure with the said damage index.